Incidence of stroke in patients with hypertrophic cardiomyopathy in stable sinus rhythm during long-term monitoring. (15th June 2023) - Fumagalli, Carlo; Bonanni, Francesca; Beltrami, Matteo; Ruggieri, Roberta; Zocchi, Chiara; Tassetti, Luigi; Maurizi, Niccolò; Berteotti, Martina; Zampieri, Mattia; Argirò, Alessia; Lovero, Fabrizio; Tomberli, Alessia; et al.
Abstract: Introduction: Patients with hypertrophic cardiomyopathy (HCM) are at increased risk of stroke, but the incidence and factors associated with cardioembolic events in HCM patients without atrial fibrillation (AF) remain unresolved. We determined the incidence of stroke in patients in sinus rhythm (SR) monitored with a cardiac implantable electronic device (CIED). Methods: All consecutive patients diagnosed with HCM and referred to CIED implantation with >16 years at diagnosis and ≥ 1 year follow-up post CIED implantation were retrospectively reviewed. Severe LA dilatation was defined as ≥48 mm. Patients were stratified by rhythm as: Pre-existing AF (AF present prior to CIED); De novo AF (AF present after CIED implantation); SR : no episodes of AF. Results: Of 1651 patients, 185 (11.2%) implanted with a CIED were included (57% men, age: 54 ± 17 years). Baseline, pre-existing AF was present in 73 (39%) patients. Ischemic stroke was reported in 19 (10.3%, 1.78%/year) patients and was similar across the three groups (2.3%/year vs 1.1%/year vs 0.6%/year in patients in SR vs pre-existing AF vs de novo AF, respectively, p = 0.235). In SR patients, a LAD≥48 mm posed the greatest risk of stroke (Hazard Ratio: 10.03, 95% Confidence-Interval 2.79–16.01). At Cox multivariable analysis, after adjustment for oral anticoagulation, LA was independently associated with stroke while rhythm was not. Conclusions: in HCM patients with CIED long-term monitoring and no prior history of AF, stroke rates were similar in those with de novo AF or stable SR. Severe LA dilatation was a powerful risk factor, irrespective of AF. Graphical abstract: CIED: Cardiac Implantable Electronic Device, HCM: Hypertrophic Cardiomyopathy, HR: Hazard Ratio, P/LP pathogenic/likely pathogenic variant. Unlabelled Image Highlights: Incidence of cardioembolic events in HCM patients with atrial fibrillation (AF) and sinus rhythm (SR) remains unresolved. Whether left atrial (LA) disease could predispose to cardioembolic events in patients with SR is undetermined. In patients with HCM and long-term monitoring stroke rates were similar in those with AF and SR. LA dilatation was a powerful risk factor.